A study on the agricultural mechanization in selected farms of Thakurgaon Sugar Mill (Bangladesh Journal of Agricultural Research, 2010)
Mechanized cultivation plays significant role in sugarcane production in Bangladesh. A study was conducted in the Thakurgaon Sugar Mill farms in Thakurgaon District as an undergraduate project work in the Department of Farm Power and Machinery, Bangladesh Agricultural University, Mymensingh. The objective was to determine benefit-cost analysis of those farms. The farm management provided data on production cost and income for the year 2001-2002. On the basis of the supplied data, it was found that the three production farms were incurring loss and the experimental farm was found to be earning marginal profit. In this study, it was observed that the farms were spending huge amount on personnel and maintenance, which is probably peculiar nature of public enterprises. Bringing available land under production, adoption of more machines to reduce labour costs, and adoption of high yielding varietys appeared to be a partial solution to reduce the huge loss and to go for profit earning. Keywords: Agricultural mechanization; farm implements; Thakurgaon Sugar Mill. DOI: 10.3329/bjar.v35i1.5879Bangladesh J. Agril. Res. 35(1) : 167-177, March 2010